Indocyanine Green Labels an Orthotopic Nude-Mouse Model of Very-Early Colon-Cancer Liver Metastases - TASHIRO, YOSHIHIKO (In Vivo, 2020)
Background/Aim: Near-infrared (NIR) fluorescence imaging using indocyanine green (ICG) is used to visualize colon-cancer liver metastases (CCLM) during surgery. The present study aimed to use ICG to visualize small CCLM in an orthotopic mouse model. Materials and Methods: A 3-mm fragment of HT29 human colon cancer was implanted to the liver of 5 athymic nude mice (nu/nu). The Pearl Trilogy Small Animal Fluorescence Imaging system was used 24 h after intravenous (IV) injection of 0.025 mg (0.25 mg/ml) ICG. Results: In four of the five mice, tumor fluorescence was detected. Small tumors (approximately 3 mm) were distinctly visualized with a minimal fluorescence liver signal, with a mean tumor to liver signal ratio of 1.81 (SD±0.167). Conclusion: Small CCLM can be clearly identified by ICG fluorescence in an orthotopic nude-mouse model. This model is translatable to the clinic for the detection of occult early CCLM.